Investigating Stress and Sources of Stress Among Female Health Profession Students in a Saudi University - Al-Qahtani MF; Alsubaie ASR (Journal of Multidisciplinary Healthcare, 2020)
Mona Faisal Al-Qahtani, Ali Saad R Alsubaie Department of Public Health, College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi ArabiaCorrespondence: Mona Faisal Al-QahtaniDepartment of Public Health, College of Public Health, Imam Abdulrahman Bin Faisal University, PO Box 2435, Dammam 31441, Kingdom of Saudi ArabiaTel +966 50 498 1410Email malqahtani@iau.edu.saBackground: Health profession students experience tremendous levels of stress throughout their education. A high level of stress may have a negative effect on the cognitive functioning and learning of students.Objective: The study sought to determine the levels and main sources of stress and its possible correlation with academic performance in the preclinical female health profession.Methods: The cross-sectional design involved the use of self-administered questionnaires. Data were collected from 260 students in health profession programmes in Saudi Arabia. The Medical Student Stressor Questionnaire (MSSQ) was used to collect the data from all second-, third-, and fourth-year undergraduate students.Results: A high level of stress was observed in 42.7% of the students, and a moderate stress level was observed in 41.5% of the students. The major source of stress experienced by students was related to the academic domain (mean= 2.7± 0.73), followed by the group activity domain (mean= 2.1± 0.91; p< 0.05). Second-year and third-year students were significantly less likely to show high stress levels compared with fourth-year students (AOR= 0.3; 95% CI: 0.1– 0.8; p≤ 0.030 and AOR= 0.4; 95% CI: 0.1– 0.5; p≤ 0.001, respectively). High stress levels were not found to be associated with students’ age and academic performance.Conclusion: Half of the students experienced high and severe levels of stress. Academic and group activity domains were perceived as the major stressors. The year of study was the only significant factor associated with stress levels. Stress among female health profession students should be acknowledged, and efforts should be made to alleviate it. Students should be guided to reduce their stress levels, as this can enhance their quality of life and study experience.Keywords: academic performance, female, health profession, students, stress, university